Disruptive Youth: Toward an Ethnographic Turn in Youth Ministry - Raffety, Erin (Ecclesial practices, 2017)
This article explores the problem of youth from the multidisciplinary viewpoints of Youth Ministry and Childhood Studies, arguing that while Youth Ministry has been limited by paradigms of developmentalism and hampered by theological essentialism, theories of childhood as a social construct and children as social actors in Childhood Studies have yet to penetrate Youth Ministry or influence society. Anticipating the potential for Youth Ministry to serve as a field for new concepts of youth, the authors posit that an ‘ethnographic turn,’ or an ethical re-orientation toward the ‘Other-ness’ of youth might allow adults to be powerfully ‘disrupted’ by God’s action in youth in the world. As such, an ‘ethnographic turn’ in Youth Ministry serves both to complement the ‘theological turn’ by providing a practical method for accessing youth experience in relationship and to critically refine Childhood Studies’ theory of child agency and failure to effect contemporary society.